Studying the effect of processing parameters on the microstructure, strength, hardness, and corrosion characteristics of friction stir dissimilar welded AA5083 and AA7075 aluminum alloys reinforced with Al-SiC matrix - Noha M. Abdeltawab; Mohamed Elshazly; Ahmed Y. Shash; M. El-Sherbiny (Heliyon)
The complementary properties of corrosion resistance and ballistic resistance of AA5083 and AA7075, respectively, explain the significance of welding these two alloys in the marine armor industry. This study investigates a novel Al-SiC matrix reinforcement with a different SiC weight ratio in dissimilar friction stir welding of the AA5083/AA7075 joint at different transverse and rotational speeds. The study deduced that the novel matrix can play an important role in improving strength and ductility simultaneously. Maximum strength takes place under conditions of 50 % SiC in Al-SiC matrix, 900 rpm rotational speed, and 40 mm/min transverse speed of value 209.8 MPa, which is equal to 90 % strength of the base metal AA5083, and the maximum strain takes place at 25 % SiC in Al-SiC matrix, 900 rpm rotational speed, and 20 mm/min transverse speed, with improved strain by 2 % than the softer alloy AA5083. Corrosion weight loss decreased by increasing the SiC weight ratio in the Al-SiC matrix, where it improved by 47.9 % compared to the base metal alloy of AA5083 at 75 % SiC in the Al-SiC matrix, 900 rpm rotational speed, and 20 mm/min transverse speed.